Altura de pré-pastejo dos capins Marandu e Convert HD 364 - Oliveira, Edimar Barbosa de (2016)
This study aimed to identify if the convert HD 364 grass should be handled in the same time pre-grazing marandu grass, through evaluation of production characteristics, structural and bromatological. The design was completely randomized design, in a 2x4 factorial with six replications, two grasses (Marandu and Convert HD 364) and four times the pre-grazing (30, 45, 60 and 75 cm) during the transition period water-dry. Neutral detergent fiber content (P <0.0360), tiller mass (P <0.0000) were higher for 75 cm height for both grasses. Marandu grass had the largest tiller mass in the height 75 cm (2.67 g). The leaf blade ratio:pseudoculm was lower (P <0.0044) with increasing heights of pre-grazing. To the heights of 30 and 45 cm the convert grass showed higher leaf blade ratio:pseudoculm 5.91 and 3.28. There was increase neutral detergent fiber (P <0.0000) and fiber indigestible neutral detergent fiber (P <0.000) and decrease in tillers density (P <0.0015), foliar leaf mass (P <0.0000), ash content (P <0.0003) and crude protein (P <0.0000), according to the increase pre-grazing height for both grasses. At the cutting heights 30 and 75 cm have greater heights dry matter production (P <0.0000) was 9481 and 10363 kg ha1 . For both grasses and in order to obtain production and quality, it is recommended to use 30 cm for pre-grazing height.